Relationship between dental anxiety levels and oral health among dental patients in Turkey: a cross-sectional study - Zafer Saba; Gunseli Katirci (BMC, 2023)
Abstract Background This study aimed to determine the relationship between dental anxiety and oral health in adult patients who applied to the Department of Restorative Dentistry at the Faculty of Dentistry at Suleyman Demirel University. Methods The study included 500 subjects. The dental anxiety levels of the patients were determined using a modified dental anxiety scale (MDAS). Information on sociodemographic details, oral hygiene and nutritional habits were recorded. Intraoral examinations of the subjects were performed. Caries prevalence of individuals was determined using the decayed, missing or filled teeth (DMFT) and decayed, missing, or filled surfaces (DMFS) indices. Gingival health was evaluated using the gingival index (GI). Statistical analyses were performed using the Mann-Whitney U, Kruskal-Wallis and Chi-square tests and Spearman correlation analysis. Results The ages of the 276 female and 224 male participants ranged from 18-84 years. The median MDAS value was 9.00. The median DMFT and DMFS values were 10.00 and 23.00, respectively. The median MDAS values ​​of women were higher than those of men. Individuals who postponed their appointment had a higher MDAS median value than those who did not (Mann-Whitney U test, p < 0.05). No statistically significant correlation was found between dental anxiety level (MDAS) and GI, DMFT and DMFS index scores (Spearman correlation analysis, p > 0.05). Conclusion The MDAS values of individuals who did not remember the reason for their dental visit were higher than those who visited the dentist for routine control. Based on the findings of this study, further research on the relationship between dental anxiety and oral health is necessary to determine the factors that pose a risk for dental anxiety and to ensure the regular benefits of dental services.